Overcoming the Dilemma between the Clarity and Flexible Norms in Environmental Offenses - Mahrus Ali (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2022)
Environmental offences are phrased abstractly and flexibly due to the standards developed by other administrative bodies with environmental responsibilities. The phrasing violates the lex certa principle that an offence must be defined clearly with not more than one interpretation. People easily grasp well-defined transgressions and know the penalties for violating them. Therefore, this study aimed to formulate a balance between flexibility and clarity in environmental offences using doctrinal legal research with the statute and conceptual approaches. The findings showed that the design representing this balance includes leaving technical and environmental offences to government regulation while including the essential elements in the Act. Administrative officials are granted the discretionary ability to determine a criminal act on these technical matters. However, this discretionary window must not violate the principles of reason and proportionality to maintain clarity and legal certainty. Science would make a formula for an offence currently considered unclear and obvious. The results also indicated that a legal rule's clarity is determined by its phrasing and the underlying notion of justice. This study was limited to identifying the formula for bridging the gap between hard and flexible norms while defining environmental crimes. Therefore, future studies could explore how law enforcement officers understand environmental crimes supported by administrative demands or obligations covered by the law.